Determinants of childhood blood pressure using structure equation model: the CASPIAN–V study - Pooneh Angoorani; Shayan Mostafaei; Toktam Kiani; Hanieh-Sadat Ejtahed; Mohammad Esmaeil Motlagh; Gita Shafiee; Armita Mahdavi Gorabi; Mostafa Qorbani; Ramin Heshmat; Roya Kelishadi (BMC Cardiovascular Disorders, 2020)
Abstract Background Childhood hypertension is a predictor of later diseases, increases the risk for cardiovascular morbidity and mortality in adulthood and results in major economic burdens. The purpose of this study was to investigate the direct and indirect effect of anthropometric, socioeconomic and lifestyle factors on blood pressure (BP) in a large population-based sample of children and adolescents using a path analysis. Methods This multi-centric nationwide study was performed on students aged 7–18 years. Anthropometric indices and blood pressure were measured by standard methods and demographic data, socioeconomic status, dietary habits and health related behaviors were obtained using validated questionnaires. Path analysis was applied to evaluate the relationships among the study variables and to implement the subsequent structural modeling. Results Totally, 7235 students (50.6% boys; the mean age 12.3 ± 3.1 years) were assessed. Systolic and diastolic BP positively correlated with age (r = 0.35 and 0.26; respectively), BMI (r = 0.06 and 0.04; respectively) and WC (r = 0.05 and 0.03; respectively). According to path analysis, age had significant direct effect on BMI, WC, and BP (β = 0.035, 0.043 and 0.345; respectively), which was greater for BP. BMI and WC had the greatest direct effect on BP (β = 0.05 and 0.03; respectively). Education level, subjective health complaints, health-related behaviors and dietary habits had positive direct effects on BP (β = 0.036, 0.030, 0.018 and 0.017; respectively). Socioeconomic status and positive changes in diet had negative indirect effect on BP (β = − 0.001 for both). Conclusion Our findings strengthen the importance of weight and body composition in BP control. It is suggested to improve diet and health related behaviors especially in families with low socioeconomic position.